Evaluating the impact of a change in the ICMS tax law in the state of Ceará in municipal education and health indicators - Francis Carlo Petterini; Guilherme Diniz Irffi (EconomiA, 2013)
In 2007 the Brazilian state of Ceará changed its law of ICMS to share resources via outcome indicators in health, education and environment. This paper evaluates and discusses the impact of this change. For this, we use the municipalities of Bahia as a control group to estimate treatment effects using differences in differences models. The results indicate a positive impact on students' proficiency in standardized tests of Portuguese and mathematics. – – Em 2007 o Ceará modificou sua Lei do ICMS rateando a quota-parte municipal via indicadores de resultado em saúde, educaç\~ao e meio ambiente. Este artigo avalia e discute o impacto desta mudança. Para tanto, utiliza os Municípios Bahia como grupo de controle para estimar efeitos de tratamento através de modelos de diferenças em diferenças. Os resultados apontam impactos positivos na proficiência dos alunos das redes municipais em exames padronizados de português e matemática.
Keywords: H75; K32; 330; Impact evaluationICMS; Mechanism design